Observational cohort study of neurological involvement among patients with SARS-CoV-2 infection. (February 2021) - Fleischer, Michael; Köhrmann, Martin; Dolff, Sebastian; Szepanowski, Fabian; Schmidt, Karsten; Herbstreit, Frank; Güngör, Cansu; Stolte, Benjamin; Steiner, Katharina Marie; Stadtler, Christine; Riße, Joachim; Fiedler, Melanie; et al.
Background: A growing number of reports suggest that infection with SARS-CoV-2 often leads to neurological involvement; however, data on the incidence and severity are limited to mainly case reports and retrospective studies. Methods: This prospective, cross-sectional study of 102 SARS-CoV-2 PCR positive patients investigated the frequency, type, severity and risk factors as well as underlying pathophysiological mechanisms of neurological involvement (NIV) in COVID-19 patients. Results: Across the cohort, 59.8% of patients had NIV. Unspecific NIV was suffered by 24.5%, mainly general weakness and cognitive decline or delirium. Mild NIV was found in 9.8%; most commonly, impaired taste or smell. Severe NIV was present in 23.5%; half of these suffered cerebral ischaemia. Incidence of NIV increased with respiratory symptoms of COVID-19. Mortality was higher with increasing NIV severity. Notably, 83.3% with severe NIV had a pre-existing neurological co-morbidity. All cerebrospinal fluid (CSF) samples were negative for SARS-CoV-2 RNA, and SARS-CoV-2 antibody quotient did not suggest intrathecal antibody synthesis. Of the patients with severe NIV, 50% had blood–brain barrier (BBB) disruption and showed a trend of elevated interleukin levels in CSF. Antibodies against neuronal and glial epitopes were detected in 35% of the patients tested. Conclusion: Cerebrovascular events were the most frequent severe NIV and severe NIV was associated with high mortality. Incidence of NIV increased with respiratory symptoms and NIV and pre-existing neurological morbidities were independent risk factors for fatality. Inflammatory involvement due to BBB disruption and cytokine release drives NIV, rather than direct viral invasion. These findings might help physicians define a further patient group requiring particular attention during the pandemic.